(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
The aim of the present study is to examine how Hungarian society thought about the roles, responsibilities and educational opportunities of women in the first half of the 20th century. In presenting the opinions, we used two press products: Vasárnapi Újság and Magyar Pedagógia. The selected articles, arranged around major nodes, outline well the expectations of women in this period. The two perceptions of women and the quotations from the newspapers point out how society was divided into two parts on issues concerned women.